FOVEAL AVASCULAR ZONE AREA AFTER INTERNAL LIMITING MEMBRANE PEELING FOR EPIRETINAL MEMBRANE AND MACULAR HOLE COMPARED WITH THAT OF FELLOW EYES AND HEALTHY CONTROLS. Issue 9 (September 2018) - Kumagai, Kazuyuki; Furukawa, Mariko; Suetsugu, Tetsuyuki; Ogino, Nobuchika
Abstract : Purpose: To measure the foveal avascular zone (FAZ) area after internal limiting membrane (ILM) peeling and to determine the factors significantly correlated with the FAZ area. Methods: This was a retrospective, observational, and cross-sectional study. The affected and normal fellow eyes of 102 patients with unilateral macular diseases and 169 healthy subjects were studied. The patients underwent successful vitrectomy with internal limiting membrane peeling for an epiretinal membrane (n = 56) or a macular hole (n = 46). The superficial FAZ area and average foveal (within 1 mm) thickness were measured. The main outcome measures were the en face FAZ area measured in the optical coherence tomography angiographic images. Results: The FAZ area in the epiretinal membrane group (0.148 ± 0.094 mm 2 ) and in the macular hole group (0.255 ± 0.111 mm 2 ) were significantly smaller than that in the healthy control group (0.358 ± 0.118 mm 2 ; all, P < 0.0001). Multiple regression analysis showed that a thicker fovea was significantly correlated with a smaller FAZ area in the epiretinal membrane group (r = −0.799, P < 0.0001), macular hole group (r = −0.473, P = 0.0042), and control group (r = −0.612, P < 0.0001). Conclusion: The FAZ area after internal limiting membrane peeling was smaller than that of the controls. A smaller FAZ area was correlated with a thicker fovea both in internal limiting membrane–peeled eyes and normal eyes. Abstract : This was a retrospective study of 56 epiretinal membrane and 46 macular hole eyes that underwent vitrectomy with internal limiting membrane peeling. The superficial foveal avascular zone area in the epiretinal membrane and macular hole eyes were smaller than that of the control eyes, and were significantly correlated with a thicker fovea in the internal limiting membrane peeled and normal eyes.